Reactions in Monolayers: The Oxidation of Thiol to Disulfide at Various Initial Surface Pressures - G. Mathapa, Baghali; Ahmad , Jamil (Asian Journal of Chemistry, 2010)
Oxidation of 1-octadecanethiol monolayer on air-water interface by acidified potassium hexacyanoferrate(III) contained in the sub-phase is described. Since the surface pressure for the compressed monolayer of the thiol depends linearly on its surface concentration, the rate of this reaction can be studies by following the decrease in surface pressure with time. For intermediate values of the initial surface pressures, the pseudo-zero order rate constant varies within a relatively narrow range (< ± 7 %). In extremely compressed monolayers, the reaction is slower by up to 60 %. This has been interpreted in terms of a squeezing out of the sub-phase oxidant from the monolayer region as well as the unfavourable orientation of the reacting thiol group.